Optimization of Fermented Rice Straw Utilization for Sustainable Beef Cattle Feeding Systems: An IPA–CSI Approach - Khalidin Khalidin; Safrika Safrika; Khairul Murdani (ITScience (Information Technology and Science), 2026)
Rice straw is an abundant agricultural by-product with considerable potential as an alternative feed resource for beef cattle, supporting sustainable crop–livestock integration and reducing dependence on natural forage. However, its utilization remains limited due to low adoption of fermentation technology and traditional extensive livestock management practices. This study aimed to identify priority strategies to optimize the utilization of fermented rice straw in sustainable beef cattle production systems. A quantitative survey was conducted using probability sampling. Primary data were collected through field observations, structured interviews, and questionnaires employing a four-point Likert scale. Data were analyzed using descriptive statistics, Importance–Performance Analysis (IPA), conformity level analysis, and the Customer Satisfaction Index (CSI). The IPA results identified several priority attributes requiring improvement, including year-round straw availability, farmers’ knowledge of fermentation techniques, ease of straw processing, cost efficiency, the use of straw as the primary feed source, and the reduction of free-grazing practices. Attributes related to feed-processing equipment availability and regular stall feeding demonstrated satisfactory performance and should be maintained. The CSI score of 44.35% indicated that farmers were generally dissatisfied with the current utilization of fermented rice straw, reflecting gaps between expectations and actual implementation. These findings suggest that optimizing the utilization of fermented rice straw requires integrated interventions, including practical fermentation training, demonstration plots, continuous extension services, institutional strengthening of farmer groups, and the development of community-based feed enterprises. Such strategies are expected to improve technology adoption and support more sustainable and intensive beef cattle production systems.